Peter’s Immature Attitude in His Ambivalent Attachment in Sara Pennypacker’s PAX: Journey Home Novel - Suyaji, Fransisca Irndianis Magdalena; Pasopati, Rommel Utungga (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study examines the portrayal of immature attitude as a manifestation of ambivalent attachment in Peter, in the novel PAX: Journey Home by Sara Pennypacker. Using John Bowlby’s attachment theory and a qualitative research approach, the study analyzes Peter’s emotional struggles, highlighting his dependency, impulsive reactions, and difficulty processing loss. His immature attitude is reflected in his self-doubt, emotional instability, and avoidance of painful memories, all of which comes from unresolved grief and inconsistent emotional support. However, as the novel progresses, Peter’s journey illustrates the potential for emotional growth through self-reflection and meaningful connections. This study highlights the role of attachment experiences in shaping emotional maturity and highlights the process of overcoming immaturity through personal development.